Trichothecenes from an Endophytic Fungus Alternaria sp. sb23 - Gao, Ying; Zhou, Jia; Ruan, Hanli (Planta Medica, 2020)
Three new (alterchothecenes A – C, 1 –3) and 3 known (4 –6) trichothecenes, along with 9 known compounds (7 –15), were isolated from the culture of Alternaria sp. sb23, an endophytic fungus separated from the root of Schisandra sphenanthera Rehd. et Wils. Their structures were elucidated by spectroscopic analyses, and the absolute configurations of 1–3 were determined through comparison of the experimental electronic circular dichroism (ECD) spectra and optical rotations with similar analogues. In vitro cytotoxicity tests of compounds 1–6 against human HT-29 colon carcinoma and human MCF-7 breast cancer cell lines indicated that 4–6 exhibited significant cytotoxic effects, with IC50 values ranging from 0.89 to 9.38 µM. And the potential of compounds 1–6 as tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) sensitizers in HT-29 cells was evaluated. The results revealed that combination treatment of TRAIL with compounds 1–6 synergistically decreased cell viability compared with the sole treatment with those compounds.
Keywords: Alternaria sp.; endophytic fungus; trichothecenes; cytotoxic effects; TRAIL sensitizer